HUBUNGAN KEJADIAN SEPSIS BERDASARKAN SKOR PEDIATRIC SEQUENTIAL ORGAN FAILURE ASSESSMENT (PSOFA) DENGAN MORTALITAS PADA PASIEN ANAK - Cahyani, Reztika; Deli, Hellena; Erwin, Erwin (Coping: Community of Publishing in Nursing; Vol 10 No 1 (2022): Februari 2022DO - 10.24843/coping.2022.v10.i01.p01, 2022)
Sepsis has a 25% incidence rate of patients in PICU. This study aims to determine the relationship between the incidence of sepsis based on the Pediatric Sequential Organ Failure Assessment (PSOFA) score with mortality in pediatric patients treated in the PICU. The research design is a retrospective study with purposive sampling technique. The sample was 89 respondents with inclusion criteria, age 1 month-17 years, PICU length of stay >24 hours, complete laboratory results, exclusion criteria were patients with chronic disease with malignancy, hematological disorders, heart, lung, congenital kidney and data were not legible. The analysis used bivariate analysis chi-square. The majority of respondents are male 57 respondents (64%), infant age (0-11 months) 33 respondents (37.1%), length of stay ? 3 days 64 respondents (71.9%) and medical diagnosis postsurgical recovery 37 respondents (41.6%), sepsis 45 respondents (50.6%) and leaving the PICU with living conditions 74 respondents (83.1%). Bivariate analysis results the p value= 0.001 is smaller than thevalue of alpha 0.05 (p value <? ). There is a significant relationship between the incidence of sepsis based on the Pediatric Sequential Organ Failure Assessment (PSOFA) and mortality. PSOFA can be used as sepsis detection methods to predict mortality in children.